Knightfall : Knight Ridder and how the erosion of newspaper journalism is putting democracy at risk - Merritt, Davis (AMACOM--American Management Association, 2005)
With corporate balance sheets dictating what we read, freedom of speech is in peril -- and freedom itself may be compromised.